Impact of the drying air conditions on the milling quality of a long-grain rice variety at different moisture content ranges using a lab-scale dryer - Garcia-LLOBODANIN, Laura; BILLIRIS, Alejandra (Food Science and Technology, 2024)
During the harvest season, rice needs to be dried immediately to prevent deterioration. Therefore, the rice industry must have the capacity to dry fast while minimizing the milling quality loss. The aim of this study was to assess the impact of drying processing variables on milling quality and drying duration, at different stages of drying. To this purpose, a thin-layer lab-scale dryer was used at different drying air temperatures, relative humidities (RH), and grain moisture content (MC) ranges. At MC up to 15%, it was possible to dry at a temperature of 47ºC and 27% RH maintaining a low milling quality loss. At lower MC, the drying air temperature should decrease to 35ºC and 50% RH to maintain the milling quality loss low. This condition increases the drying duration (compared with drying at 47ºC). Therefore, a two-stage drying program was proposed, using more severe drying conditions during the first stage (MC up to 15%) and softening the conditions during the final stage (MC from 15 to 13%). This drying program allows decreasing the drying duration, maintaining a low milling quality loss. The implementation of step-wise drying programs is expected to increase the efficiency of the commercial process.